Characterization by Photocurrent Spectroscopy of Anodic Films Formed on Tin-Indium Alloys - Moina,Carlos (2009)
In the present work, a study of the photoelectrochemical characteristics and chemical structure of anodic films formed onto different Sn1-xIn x (0 ≤ x < 0.3) alloys in 0.2 M NaOH is presented. The electrochemical behavior of the alloys was studied by means of cyclic voltammetry. The optical band gaps of the passive films were determined by photocurrent spectroscopy, while its chemical structure was studied by Fourier transform infrared reflection-absorption spectroscopy. The experimental results indicate that the anodic films consist of hydroxylated species of the type In ySn(1-y)(OH)4-y. The films are enriched in In and, for x > 0.25, In(OH)3 is the dominant component of the surface layers. The existing theoretical background was used to estimate the relative concentration of Sn and In in the films from the band gap measurements.